2011
DOI: 10.1002/job.783
|View full text |Cite
|
Sign up to set email alerts
|

Individualism–collectivism and team member performance: Another look

Abstract: Summary This study revisits the commonplace research conclusion that greater team member collectivism, as opposed to individualism, is associated with higher levels of individual‐level performance in teams. Whereas this conclusion is based on the assumption that work in teams consists exclusively of tasks that are shared, typical teamwork also includes tasks that are individualized. Results of a laboratory study of 206 participants performing a mix of individualized and shared tasks in four‐person teams indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 75 publications
1
26
0
1
Order By: Relevance
“…Some scholars (e.g., Chen et al, 1998;Earley & Gibson, 1998;LePine, Hanson, Borman & Motowidlo, 2000) have suggested, because of the emphasis collectivists place on shared responsibility, collectivism should be related positively to team performance. A number of studies (e.g., Campion et al, 1993;Eby & Dobbins, 1997) have provided empirical support for this contention prompting some scholars (e.g., Driskell & Salas, 1992;Miles, 2000) to conclude that a collectivistic orientation likely influences the performance of individuals in teams (Wagner, Humphrey, Meyer & Hollenbeck, 2012).…”
Section: Psychological Collectivismmentioning
confidence: 99%
“…Some scholars (e.g., Chen et al, 1998;Earley & Gibson, 1998;LePine, Hanson, Borman & Motowidlo, 2000) have suggested, because of the emphasis collectivists place on shared responsibility, collectivism should be related positively to team performance. A number of studies (e.g., Campion et al, 1993;Eby & Dobbins, 1997) have provided empirical support for this contention prompting some scholars (e.g., Driskell & Salas, 1992;Miles, 2000) to conclude that a collectivistic orientation likely influences the performance of individuals in teams (Wagner, Humphrey, Meyer & Hollenbeck, 2012).…”
Section: Psychological Collectivismmentioning
confidence: 99%
“…The challenge for organisations is to create the balance between collaborative and competitive tendencies for individuals within their firms. This is at the heart of how firms can optimise human resource efforts in support of the firm's objectives (Wagner, Humphrey, Meyer & Hollenbeck, 2012). This study examines the effectiveness of combining team design and incentive methods to increase the performance levels of staff over time.…”
Section: Introductionmentioning
confidence: 99%
“…Firms tend to structure financial incentives in the hope they will support their desired outcomes (Jenkins et al, 1998;Wagner et al, 2012). Part of the intention in the deliberate structuring of rewards by firms is to support the necessary level of interdependencies within and among teams, and among individuals (Jenkins, et al, 1998;Wageman, 1995;Wagner, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations